2015
DOI: 10.3189/2016aoj71a008
|View full text |Cite
|
Sign up to set email alerts
|

A satellite-derived glacier inventory for North Asia

Abstract: ABSTRACT. This study outlines a consistent methodology for identifying glacier surfaces from Landsat 5, 7 and 8 imagery that is applied to map all mainland North Asian glaciers, providing the first methodologically consistent and complete glacier inventory for the region �2010. We identify 5065 glaciers covering a planimetric area of 2326 � 186 km 2 , most of which is located in the Altai mountain subregion. The total glacier count is 15% higher, but the total glacier area is 32 � 11.6% lower, than the estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Differences in the estimates of glacial areas obtained by us and other researchers (Table 8) are due to several reasons, as follows. It should be noted that no special survey or article devoted to the results for Tavan Bogd has yet appeared for the data that were obtained within the framework of the RGI 5.0/GLIMS database for the northern slope [74,75] and the "Second Glacier Inventory of China" [76,77] for the western slope.…”
Section: Recent Glacier Extent Of Tavan Bogd and Comparison Between Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the estimates of glacial areas obtained by us and other researchers (Table 8) are due to several reasons, as follows. It should be noted that no special survey or article devoted to the results for Tavan Bogd has yet appeared for the data that were obtained within the framework of the RGI 5.0/GLIMS database for the northern slope [74,75] and the "Second Glacier Inventory of China" [76,77] for the western slope.…”
Section: Recent Glacier Extent Of Tavan Bogd and Comparison Between Dmentioning
confidence: 99%
“…Difference between perennial snowfields and small glaciers (diagnostic signs of glaciers, such as crevasses and presence of zones of accumulation and ablation) is not always clearly seen in satellite images, and the same objects can be treated differently by one or the other class of objects. A relatively high area of the glaciers given in the RGI 5.0/GLIMS database [74,75] for the Russian portion of the massif is a good example of overestimation of glacial area due to misinterpretation of perennial snow patches. In our previous article [73] we gave an example of differences between our results of delineation of the glaciers of the northern slope of Tavan Bogd and the results from the RGI 5.0/GLIMS database [74,75].…”
Section: Recent Glacier Extent Of Tavan Bogd and Comparison Between Dmentioning
confidence: 99%
“…In the 21st century, the development of remote sensing, sometimes in combination with in situ observations, led to a number of new publications: [31][32][33][34][35][36][37][38][39] The Mongolian glaciers have been cataloged and mapped by Kamp et al [34,40]. Recently the glaciers of the region were included in the GLIMS (Global Land Ice Measurements from Space) database and the Randolph Glacier Inventory [34,41,42]. The materials of the field observations were obtained for Turgen [33], Tavan Bogd, and Tsambagarav [37,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…This accuracy value is in the range of that obtained from other mountain regions [11,13,14]. Fisher et al [15] found that the errors when using medium resolution images increase with decreasing glacier size and for small glaciers (<0.5 km 2 ) can exceed 25%.…”
Section: Discussionmentioning
confidence: 65%